Developing PBL E-Learning with the Brainwriting Method to Improve HOTS and Learning Interest in the Circulatory System - Aulya, Rahmi; Ariyanti, Nur Aeni (Jurnal Pendidikan Matematika dan Sains, 2026)
This study aims to determine the feasibility, practicality, and effectiveness of PBL e-learning using the brainwriting method to enhance students’ Higher-Order Thinking Skills (HOTS) and learning interest. This research employs a research and development approach using the ADDIE  model. The research instruments included media validation sheets from material and media experts, questionnaires, observation sheets, and test questions. The research results are as follows: (1) PBL e-learning with the brainwriting method is feasible for enhancing students’ HOTS and learning interest; (2) this e-learning is practical for use in learning activities, as indicated by assessments from students and teachers, with a practicality score of 98, categorized as “very practical”; and (3) this e-learning is effective in improving students’ HOTS and learning interest, as shown by the MANOVA test results, with a significance value of 0.000 (< 0.05). These findings suggest that integrating Problem-Based Learning (PBL) with the brainwriting method in an e-learning environment can be an effective instructional strategy to foster higher-order thinking skills and increase students’ engagement in biology learning. Furthermore, this study contributes to the achievement of the Sustainable Development Goals, particularly SDG 4 (Quality Education), by promoting inclusive, innovative, and technology-enhanced learning practices that support the development of critical thinking skills essential for lifelong learning in the 21st century.